1984
DOI: 10.1246/cl.1984.409
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Hydroxy Fatty Acids, the Self Defensive Substances in Rice Plant Against Rice Blast Disease

Abstract: In addition to the previously described epoxy fatty acids, five hydroxy fatty acids were characterized as self defensive substances produced in the rice plant against rice blast disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(52 citation statements)
references
References 4 publications
0
52
0
Order By: Relevance
“…From a phylogenic point of view, it is interesting that the metabolic pathway of C18-epoxides resembles that already described in higher plants (39). Interestingly, it has been shown that certain cutin monomers (i.e., 9,10,18-TriSTA), which are released from the plant cuticle by fungal cutinases, may protect the plant against fungal infection by inducing the plant defense mechanisms (2). It will be of great interest to further examine the possible metabolic and functional effects of these metabolites in mammals at the molecular and physiological levels.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…From a phylogenic point of view, it is interesting that the metabolic pathway of C18-epoxides resembles that already described in higher plants (39). Interestingly, it has been shown that certain cutin monomers (i.e., 9,10,18-TriSTA), which are released from the plant cuticle by fungal cutinases, may protect the plant against fungal infection by inducing the plant defense mechanisms (2). It will be of great interest to further examine the possible metabolic and functional effects of these metabolites in mammals at the molecular and physiological levels.…”
Section: Discussionmentioning
confidence: 76%
“…Epoxidized fatty acids from the C18 family (C18-epoxides) such as Z 9(10)-epoxyoctadecanoic acid [ Z 9(10)-EpSTA], Z 9(10)-epoxyoctadec-Z 12-enoic acid [ Z 9(10)-EpOME, leukotoxin], and Z 12(13)-epoxyoctadec-Z 9-enoic acid [ Z 12(13)-EpOME, isoleukotoxin] should be regarded as toxic and/or defensive substances in living beings because they have been described as toxic metabolites in mammals (1) and as defense compounds in infected plants (2,3). The conversion of fatty acid epoxides to the corresponding vicinal diol by epoxide hydrolases (EHs) is thought to be the general pathway for fatty acid epoxide clearance (4-9), although recently, Fang et al (10) reported the conversion of epoxyeicosatrienoic acid (EET) to a chain-shortened epoxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work showed that an activity that decomposed lipid hydroperoxides (LHDA) was present in rice seeds (17). The results indicated that the activity converted 1 3-HPODD (9-HPODD) to 1 3-HODD (9-HODD) and 9,10,1 3-trihydroxyoctadec-11 -enoic acid (9,12,1 3-trihydroxyoctadec-lO-enoic acid), which had antifungal activity against the rice blast fungus (10,1,17). We observed that LHDA in rice leaves also produced the hydroxy fatty acids, but it is possible that other enzymes that convert lipid hydroperoxides to their special products are present in the fungus-infected leaves.…”
Section: Antifungal Activities Of Hydroperoxy and Hydroxy Fatty Acidsmentioning
confidence: 99%
“…LOX has been found to participate in the synthesis of hydroperoxy fatty acids as exemplified in the case of linolenic acid (1), which is oxidized to a hydroperoxy derivative (2) by the action of LOX and oxygen molecules. The corresponding allyl alcohol (3), the main anti-rice blast fungus substance isolated from infected rice plants, has a strong inhibitory activity toward germination of rice blast fungus while 2 has quite powerful cytotoxicity to rice leaves as well as an anti-blast fungus activity.2,3) Thus the LOX activity increment has been proposed to be correlated with the defense of rice plants against rice blast disease.…”
mentioning
confidence: 99%